Evaluating The Content Of The Arabic Language Textbook For The Fourth Preparatory In The Light Of The Habit Of Thinking About Thinking (Metacognition) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current research aims to evaluate the content of the Arabic language textbook for the fourth preparatory in the light of thinking about thinking (metacognition). The sample consists of the Arabic language textbook for the fourth preparatory for (2019-2020). In addition, it defines the basic terms and reviews the relevant studies as well as the different theoretical aspects of the subject. The research tool is represented by a special analysis form consisting of a set of behavioral manifestations of thinking about thinking (metacognition). The validity and reliability of research tool are verified. The result shows that the Arabic language textbook contains a good habit of reason. The study provides several recommendations that can be adopted by specialists and researchers in this field as well as suggesting a number of future works representing projects and studies in this field.